Behavioral Difficulties in Adolescents With Cerebral Palsy. (January 2013) - Brossard-Racine, Marie; Waknin, Joey; Shikako-Thomas, Keiko; Shevell, Michael; Poulin, Chantal; Lach, Lucy; Law, Mary; Schmitz, Norbert; ,; Majnemer, Annette
Behavioral problems are common in children with cerebral palsy; however, little is known about the persistence of these difficulties during adolescence. This study aimed to describe the nature and frequency of behavioral difficulties in adolescents with cerebral palsy and to explore associated factors. Parents of the participants completed the Strengths and Difficulties Questionnaire. Participants' motor and cognitive abilities, functional status, as well as parental stress were evaluated. Overall, the study enrolled 160 adolescents with cerebral palsy (65 girls, mean age 15.4 ± 2.17 years). Behavioral difficulties were present in 36.9% of the adolescents, with peer problems the most frequently reported (61.9%). Prosocial behaviors were associated with better function ( r = 0.24-0.65) whereas hyperactive symptoms were associated with greater limitations ( r = –0.19 to –0.55). Weak associations were found between parental stress and externalized problems ( r = 0.22−0.24). Behavioral difficulties remained frequent in adolescents with cerebral palsy, particularly in those with greater functional limitations.